MERDEKA BELAJAR - Juli Iswanto, Fachruddin Azmi, (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2021)
Abstract: This discussion aims to increase knowledge and understanding of the freedom of learning, which is freedom in determining how to behave, process, think, apply creatively for the development of each individual by deciding his destiny. The method in this journal is to use a literature review. The Literature Review is a description of the theory, findings and other research materials obtained from reference materials to be used as the basis for research activities to develop a clear frame of mind from the formulation of the problem to be studied. The key to independent learning lies with the driving teacher, and the ambitious teacher will not be realized when they are not entirely separate. So realizing this Freedom of Learning must be done fundamentally, not just through technical matters and changing new policies. Independent Learning will be recognized when the teacher is genuinely independent, which can be achieved with several solutions. To realize independent teachers must also synergize students, families, and communities in learning. The goal is to facilitate technical knowledge. Mainly in student-centred learning, experiential learning, and classroom learning. Independent teachers with the synergy of family and community will facilitate their role as the driving force of civilization.